أصول الشرعية السياسية وتطبيقاتها المعاصرة : دراسة فقهية مقارنة في ضوء مقاصد الشريعة الإسلامية - بوشلاغم، صالح (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
This thesis seeks to study the issue of political legitimacy in the jurisprudence systems of the Sunni, Ibadhi and Shiite, and compare between the ancient and contemporary opinions based on holly texts contains and the objectives of Shari'a. The thesis consist of six chapters; the first is the preliminary chapter, while the second focuses on the concept of political legitimacy and its types, cases, and history in Islam. The third chapter extrapolates verses and hadiths related to political legitimacy as well as the objectives of Shari'a on policy. The forth chapter examines Islamic stand on political legitimacy which based on how the people give legitimacy to the governor or to the chosen political system. In the next chapter, the researcher identifies the ways of power in Islamic jurisprudence and to what extent they meet the requirement of political legitimacy. In the last chapter, the researcher examines some tools to repair political legitimacy in both peaceful and non-peaceful ways. The researcher used the indicative, descriptive analytical and comparative critical methodologies. The most important findings indicates that political legitimacy means the voluntary belief of the governed in the right of the governor. The shari'a gives importance to political legitimacy through verses of the Shura, justice and other verses which prohibit obedience to oppressive governors, based on the practices of the Prophet, the legislations and by Sharia political objectives which cannot be realized without political legitimacy. The Islamic standard of political legitimacy is the efficiency and the researcher suggests that it should be in political system, political program and efficiency of governor. The study illustrates that the way of getting power cannot be legitimate only if it takes the optional acceptance of the people. In addition, the study proves that the tools to repair political legitimacy such as armed revolution against illegitimate governor are permissible which is legislated by majority of scholars with some conditions; however, recourse of international military organization is prohibited and can only be used in forced cases.